French Flow New works by Tero Saarinen and Russell Maliphant are seen - Hutera, Donald (Dance Books Ltd., Alton,Hampshire (UK), 2005)
New works by Tero Saarinen and Russell Maliphant are seen. PALABRAS CLAVE: Tero Saarinen, Russell Maliphant, Borrowed Light, Twelvetwentyone, Mauro Bigonzetti, Frenchman Christian Rizzo.